2015
DOI: 10.18632/oncotarget.5610
|View full text |Cite
|
Sign up to set email alerts
|

A network meta-analysis of the efficacy and side effects of udca-based therapies for primary sclerosing cholangitis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 47 publications
0
7
0
3
Order By: Relevance
“…These results are consistent with our previous findings showing that UDCA aggravates liver injury in ANIT-treated model mice via the induction of BSEP ( Zhang et al, 2018 ). Thus, induction of Yinchen to BSEP expression may be deleterious in obstructive cholestasis, such as PSC with segmental biliary obstruction ( Roma et al, 2011 ; Zhu et al, 2015 ) and cholangiocarcinoma with bile duct blockage. However, our recent findings indicate that Yinchen can alleviate liver injury in 1% CA-induced cholestatic model mice via the induction of BSEP (data not shown), suggesting that Yinchen can induce BSEP to treat cholestasis when the bile duct is not obstructed.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with our previous findings showing that UDCA aggravates liver injury in ANIT-treated model mice via the induction of BSEP ( Zhang et al, 2018 ). Thus, induction of Yinchen to BSEP expression may be deleterious in obstructive cholestasis, such as PSC with segmental biliary obstruction ( Roma et al, 2011 ; Zhu et al, 2015 ) and cholangiocarcinoma with bile duct blockage. However, our recent findings indicate that Yinchen can alleviate liver injury in 1% CA-induced cholestatic model mice via the induction of BSEP (data not shown), suggesting that Yinchen can induce BSEP to treat cholestasis when the bile duct is not obstructed.…”
Section: Discussionmentioning
confidence: 99%
“…It is more hydrophilic than its structural analog, chenodeoxycholic acid, contributing in part to its beneficial effects and reduced bile acid‐induced hepatotoxicity . Unfortunately, various trials have failed to show the same beneficial effects in PSC despite some improvements in liver biochemistry . In some instances, high‐dose UDCA has even been harmful …”
Section: Clinical Trials: Translating Precision Medicine Into Practicementioning
confidence: 99%
“…Bosch et al 29 suggested that preventive administration of UDCA after liver transplantation for PBC patients reduces risk of recurrence. UDCA, as well, helps improve liver functions but has less benefit in improving prognosis for patients with primary sclerosing cholangitis (PSC) 30,31…”
Section: Therapeutic Roles Of Bas Signaling In Chronic Liver Diseasesmentioning
confidence: 99%